(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Background: Oral health literacy in early childhood plays an essential role in supporting optimal growth and development, yet oral hygiene practices among preschoolers remain low. The persistently high prevalence of dental caries among young children underscores the urgent need for early, age-appropriate educational interventions. The novelty of this community service lies in the use of interactive educational activities and dental condition identification. This interactive approach is particularly effective and innovative within the local community context. Objective: This study aimed to enhance oral health literacy among preschool children through interactive educational learning and dental condition identification. Method: The intervention consisted of interactive lectures, guided question-and-answer sessions, toothbrushing demonstrations, supervised group brushing practice, and basic dental examinations conducted by students of the Dentistry Professional Education Program, Faculty of Dentistry, Universitas Padjadjaran. A community service activity was conducted at PAUD TAAM Al-Musdariyah, Bandung, involving 29 children aged 4-6 years. Results: The interactive educational intervention increased children’s oral health literacy regarding appropriate brushing times, methods, and toothpaste amounts, although correct brushing techniques were not yet consistently achieved. Dental examinations revealed that 72.4% of the children had dental caries. Conclusion: Interactive education learning effectively enhanced young children’s understanding of oral health. The children had high dental caries. Sustained school-based education and active parental involvement are essential to establish and maintain lifelong oral hygiene habits.